Turnaround: Retrenchment and recovery - Robbins, D. Keith; Pearce, John A. (Strategic Management Journal, 1992)
Abstract Empirical research was conducted to investigate retrenchment as an integral component of the overall turnaround process. An industry study provided an anchored operational definition of a turnaround situation, indications of its internal and external causes, and an application of an absolute measure of its severity. The research further produced an empirical discrimination between retrenchment as a stand‐alone response to financial decline and retrenchment as an initial phase of a turnaround strategy, and an identification of activities that can be used to classify entrepreneurial vs. efficiency emphases in a turnaround firm's recovery response.